Comparison of Body Composition between Raiders and Defenders in Kabaddi: Muscle Mass and Fat Percentage - Triatmaja, Muhammad Wahyu; Sudijandoko, Andun; Solikah, Nur Luthfiatus; Sulistyarto, Soni; Kumaat, Noortje Anita (JSKK (Jurnal Sains Keolahragaan dan Kesehatan), 2025)
Kabaddi is a complex game with high intensity, where each player must have good aerobic and anaerobic capacity. Considering the playing position, body composition needs to be taken into account, because ideal body composition is a determining factor in an athlete's performance. This study aims to determine the body composition of kabaddi players and compare the characteristics of muscle mass (kg) and fat percentage (%) between raiders and defenders. This study uses a comparative quantitative method with a sample size of 19 kabaddi athletes from East Java. Body composition measurements were taken using InBody H20, which measures muscle mass and fat percentage. Data analysis was performed using the t-test with the help of SPSS software. The results of this study showed that there was no significant difference in muscle mass between raiders and defenders (p=0.223), and there was no significant difference in fat percentage (p=0.930). The conclusion is that even though the raider and defender positions have different roles, the balance between muscle mass and body fat percentage is one of the factors that supports optimal performance. Due to the complementary and dynamic playing patterns in kabaddi, athletes from both positions have almost equivalent physical requirements, which leads to similar body compositions. Keywords: kabaddi, body composition, muscle mass, fat percentage